On (h,m)-Convex Functions and Inequalities - Valdés, Lucas Gómez, Juan E. Nápoles (Discontinuity, Nonlinearity, and Complexity, 2026)
This work explores novel integral inequalities for (h,m)-convex functions using key mathematical techniques, including Hölder’s, Young’s and Power Mean inequalities. By leveraging these classical results, we establish improved bounds and extend Hermite-Hadamard type inequalities. The findings contribute to a deeper understanding of (h,m)-convex functions and their role in mathematical analysis. Additionally, we discuss particular cases to emphasize the relevance of our contributions.